ERCP (endoscopic retrograde cholangiopancreatography) and EUS (endoscopic ultrasonography) in diagnosis of choledocholithiasis – battle or cooperation? - Szymkowicz, Anna; Pałuchowska, Julia; Sambura, Maria; Rosołowska-Żak, Sara; Paschke, Patrycja; Miczek, Igor (Journal of Education, Health and Sport, 2024)
Introduction: Diagnosis of choledocholithiasis, a common manifestation of gallstone disease, is mainly based on advanced endoscopic techniques such as ERCP and EUS. Since the 1970s, ERCP has been a key method in the diagnosis and treatment of choledocholithiasis, allowing direct visualization and therapeutic interventions. However, technological developments have brought the emergence of EUS as a complementary tool, providing high-resolution imaging of the bile ducts. Understanding the diagnostic accuracy, therapeutic options and complications of both modalities is key to optimizing the care of patients with bile duct stones. Aim of the study: The aim of our study is to review and compare various diagnostic methods of bile duct stones, as well as to assess their effectiveness, accuracy, and potential complications. Materials and methods: We searched electronic sources, aspecially in the PubMed and Google Scholar databases, using keywords such as , endoscopic ultrasonography”, , endoscopic retrograde cholangiopancreatography” and , choledocholithiasis”. Conclusions: With the use of modern technologies, such as endoscopic ultrasonography (EUS) and retrograde choleangiopancreatography (ERCP), it has become possible to diagnose bile duct stones more accurately and introduce more effective and less invasive therapies. The development of the availability of diagnostic tests, especially those that do not require invasive procedures, has helped reduce the risk of complications. EUS may be the preferred tool of choice for patients with gallstones, as it is associated with a lower risk of complications compared to ERCP alone. Decisions regarding the use of specific diagnostic and therapeutic modalities should be made on a case-by-case basis, taking into account medical and economic considerations.